Knowledge, confidence, skills and practices among midwives in the republic of Ireland in relation to perinatal mental health care: The mind mothers study. (September 2018) - Carroll, Margaret; Downes, Carmel; Gill, Ailish; Monahan, Mark; Nagle, Ursula; Madden, Deirdre; Higgins, Agnes
Highlights: Midwives reported having knowledge and skills in the areas of depression and anxiety but believed they lacked knowledge and skills in many other areas of perinatal mental health. The findings suggest that midwives may need to adopt a more comprehensive approach towards assessment of women at risk and to develop skills to address the needs of partners. Abstract: Objective: The study aimed to identify midwives' competency in perinatal mental health care in terms of their knowledge, confidence, skill and educational priorities, and to explore their clinical practices in relation to the assessment and management of perinatal mental health problems. Research design: An exploratory descriptive study design was used on a sample of 438 midwives in the Republic of Ireland. Data were collected over a two-month period in 2016 using an anonymous, self-completed survey designed by the research team. Findings: The majority of midwives cared for women with perinatal mental health problems in their clinical practice; however, beyond depression and anxiety, their knowledge of perinatal mental health problems was quite limited. Similarly, midwives reported a lack of skill in opening a discussion with women on sensitive issues, such as sexual abuse, intimate partner violence and psychosis, and providing information to women's partners/families. The findings indicated that midwives adopted a selective approach to screening for perinatal mental health problems, with a tendency not to inquire about sensitive topics, or address them only with women deemed at-risk. Conclusions: Timely and appropriate care is required to ensure the best outcomes for women with perinatal mental health problems and their families. A greater understanding of perinatal mental health among midwives is required to enable them to provide support and information to women and their families, and to identify when specialist intervention is required. Education and other structural supports, such as care pathways and documentation, is required to train and support midwives in their key role of caring for, and collaborating with, women with perinatal mental health problems.